The Effectiveness of Price to Book Value in Classifying Value and Growth Stocks and Its Implications for Stock Returns in Indonesia - Kurnia Permana; Muhammad Haris Saputra (Future Science, 2025)
The distinction between value stocks and growth stocks has long been a central topic in asset pricing and investment decision-making. The Price to Book Value (PBV) ratio is one of the most frequently used valuation metrics to determine whether a stock is undervalued (value) or overvalued (growth). However, empirical evidence in emerging markets, including Indonesia, remains inconclusive, particularly regarding the performance differences between value and growth stocks. This quantitative study employs secondary data from 72 companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. PBV serves as the primary basis for classifying stocks, while ROE, DER, firm size, and stock returns are analyzed using descriptive statistics, independent-samples t-tests, and multiple regression analyses. The findings reveal that value stocks (low PBV) generate higher average returns than growth stocks (high PBV), with the difference being statistically significant (p < 0.05). Regression analysis shows that ROE has a positive and significant effect on PBV, while DER negatively affects PBV. Firm size exhibits no significant effect. These results confirm that PBV is an effective indicator for distinguishing between value and growth stocks in the Indonesian market. The study reinforces the relevance of the value premium and highlights the essential role of profitability and capital structure in determining firm valuation.